Design of Integrated School Learning Information System Using CodeIgniter Framework - Arista Pratama; Asif Faroqi; Eka Prakarsa Mandyartha (Future Science, 2022)
The development of Information and Communication Technology (ICT) requires schools to always improve the quality of learning by utilizing the use of ICT. The development of ICT in schools provides many new opportunities that can support the learning process. The use of ICT plays an important role in improving the quality of education by increasing the development of educational content, supporting administrative processes in schools, and increasing access to education for teachers and students through distance learning. Utilization of ICT in the school environment can also assist in evaluating and improving the abilities and knowledge of each student. This study aims to design an integrated school learning information system using the CodeIgniter framework. The design of the integrated school learning information system model uses the Unified Modeling Language (UML). The design of the integrated school learning information system uses the PHP programming language and MySQL as the database. Integrated school learning information system includes various features e-modules, e-daily tasks, question banks, e-tests, e-reports, and e-monitoring. Integrated school learning information system is expected to improve the quality of learning so that it can improve students' abilities and knowledge. Integrated school learning information system is also expected to make it easier to obtain information on the results of evaluating students' abilities and knowledge as well as being a medium that can improve student achievement and quality of graduation.